2019
DOI: 10.2478/jaes-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Building Construction Labour Productivity in Arid Climate Environment

Abstract: Productivity is a significant aspect of construction industry that plays vital role for success and failure of any construction project. This industry generates 11% to 13% of GDP all around the globe and the cost of labour in any building project is 20% to 35% of the cost of Building. On daily basis labour utilizes 30% of time on productive activities rest 70% of the time is ruined in non-productive activities, there are multi factors which are affecting the labour production in construction industry hence thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Table 1 shows a summary of co-occurred keywords with the total link strength between the keywords. Among the different construction activities, masonry (Arif and Khan, 2020; Bhatti et al , 2019; Chui et al , 2012; Florez and Cortissoz, 2017; Joshua and Varghese, 2011; Mao et al , 2018; Ouga et al , 2020) and formwork (Azhar et al , 2020; Bhatti et al , 2019; El-Gohary et al , 2017; Golnaraghi et al , 2019; Lee et al , 2017; Mine et al , 2015) were presented lonely or combined with other activities, the most activities monitored for their productivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows a summary of co-occurred keywords with the total link strength between the keywords. Among the different construction activities, masonry (Arif and Khan, 2020; Bhatti et al , 2019; Chui et al , 2012; Florez and Cortissoz, 2017; Joshua and Varghese, 2011; Mao et al , 2018; Ouga et al , 2020) and formwork (Azhar et al , 2020; Bhatti et al , 2019; El-Gohary et al , 2017; Golnaraghi et al , 2019; Lee et al , 2017; Mine et al , 2015) were presented lonely or combined with other activities, the most activities monitored for their productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Although traditional methods have some limitations for site monitoring, such as time-consuming, operose, missing or incomplete information, resulting in a slow flow of information, make effective decision-making difficult, labor-intensive and high expenses (Kimoto et al , 2005; Luo et al , 2018; Naoum, 2015; Omar et al , 2018; Yang et al , 2015), they have been used in several studies to monitor the productivity of different indoor activities (such as tiling, plastering, masonry work, false ceiling boarding and fixing and application of screed) and outdoor activities (such as formwork, reinforcement steel activities, MEP, concrete work and curtain wall) (Alchaer and Issa, 2020; Azhar et al , 2020; Bhatti et al , 2019; Chui et al , 2012; Florez and Cortissoz, 2017; Gouett et al , 2011; Hwang, 2010; Ko and Han, 2015; Kubečková and Smugala, 2020; Mao et al , 2018; Mine et al , 2015; Ouga et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In an emerging economy like Nigeria, Usman et al (2012) accentuate that the continue project failure being experienced in the industry are associated with poor contractors performances resulting from poor workmanship, high level of rework, low output, delay completion and cost overruns, high accident records and poor productivity of labour. Bhatti et al (2019) carried out study aim at determining the extent to which changes in arid climate environment affect variations in labour productivity. The study concluded that the higher the temperature, the lower the productivity of labour.…”
Section: Factors Motivating Labour Productivity On Construction Projectsmentioning
confidence: 99%